Hierarchical Hollow Heterostructures for Photocatalytic CO2 Reduction and Water Splitting. Issue 1 (3rd October 2019) - Wang, Sibo; Wang, Yan; Zang, Shuang‐Quan; Lou, Xiong Wen (David)
Abstract: Using solar‐driven photocatalytic systems based on semiconductor photocatalysts to produce valuable energetic fuels is attracting massive research attention due to global energy and environmental challenges. Developing highly efficient and stable photocatalysts is of decisive importance for this promising technology. Hierarchical hollow heterostructures with ultrathin two‐dimensional (2D) nanosheet subunits hold multiple intrinsic advantages for heterogeneous photocatalysis, in terms of increasing light harvesting, expediting charge separation and transfer, and boosting surface redox reactions. This review summarizes the recent developments of rationally designed hierarchical hollow heterostructures for photocatalytic CO2 reduction and water splitting in suspension systems. The advantages and progress of hierarchical hollow heterostructured photocatalysts for the solar‐fuel‐producing applications are highlighted. The challenges of further developments of hierarchical hollow heterostructures and their use in the photocatalytic applications are discussed. Some outlooks on the potential solutions are also proposed. Abstract : This review summarizes recent research progress of rationally designed hierarchical hollow heterostructures for photocatalytic CO2 reduction and water splitting. This unique class of photocatalysts has some important advantages in enhancing light absorption and photo‐generated charge separation.